2014
DOI: 10.1155/2014/857143
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dendritic Cells in Tissue-Specific Autoimmunity

Abstract: In this review, we explore the role of dendritic cell subsets in the development of tissue-specific autoimmune diseases. From the increasing list of dendritic cell subclasses, it is becoming clear that we are only at the beginning of understanding the role of these antigen presenting cells in mediating autoimmunity. Emerging research areas for the study of dendritic cell involvement in the onset and inhibition of tissue-specific autoimmunity are presented. Further, we compare tissue specific to systemic autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 159 publications
(180 reference statements)
0
51
0
Order By: Relevance
“…The key cells of the innate immune response are the dendritic cells and NK cells, and the principal cells involved in the adaptive immune response are the Th lymphocytes, gamma delta (cd) lymphocytes, and regulatory T cells (Tregs). NKT cells exhibit features of both the innate and adaptive immune responses [238][239][240]. Tregs have been the principal cell population under active investigation in autoimmune hepatitis, but NKT cells have been emerging as another population with important immune modulatory functions.…”
Section: Insights Into the Principal Cell Mediators Of Autoimmune Hepmentioning
confidence: 99%
“…The key cells of the innate immune response are the dendritic cells and NK cells, and the principal cells involved in the adaptive immune response are the Th lymphocytes, gamma delta (cd) lymphocytes, and regulatory T cells (Tregs). NKT cells exhibit features of both the innate and adaptive immune responses [238][239][240]. Tregs have been the principal cell population under active investigation in autoimmune hepatitis, but NKT cells have been emerging as another population with important immune modulatory functions.…”
Section: Insights Into the Principal Cell Mediators Of Autoimmune Hepmentioning
confidence: 99%
“…The increasing prevalence of IDDM, its progressive complications, and the lack of effective preventive and curative strategies require a greater effort to develop effective and safe methods for persistent restoration of normal blood sugar levels in IDDM patients. So far, no safe and effective treatment is available to control the onset and progression this life-long debilitating disease (3). The loss of β-cell function in IDDM is mediated principally by CD4 + and CD8 + T cells, and autoreactive effector CD8 + T cells (CTLs) were shown to be responsible for islet β-cell destruction in the non-obese diabetic (NOD) mouse and in human IDDM (46).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] In addition, CD86 and IL-12 are crucial for Th1 priming, whereas no exact mechanism for the regulation of Th2 exists. 26,27 Recent studies have indicated that DCs are associated with brotic diseases.…”
Section: Introductionmentioning
confidence: 99%